Pengungkapan Informasi Dalam Laporan Keuangan: Perspektif Stakeholder Dan Interpretasi Yang Berbeda - Nur Fitriana; Afdal Rio Andika; Ersa Lestari; Kenya Adeliani; Suci Aulia Ramadhani (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
Disclosure of information in financial statements plays a crucial role in creating transparency and accountability to stakeholders. This study aims to examine stakeholders' perspectives on information disclosure, differing interpretations, and the challenges companies face in presenting financial statements. Using agency theory and legitimacy theory as a framework, the study explores how companies can balance stakeholders' information needs with protecting their business strategies. Data were obtained through a case study approach in the manufacturing industry, utilizing qualitative and thematic analysis to identify trends. The findings reveal that both mandatory and voluntary disclosures play significant roles in meeting the diverse information needs of stakeholders, including investors, creditors, employees, and the public. However, challenges such as information asymmetry, regulatory complexity, and the risk of misinformation need to be carefully managed. The study concludes the importance of a strategic approach in information disclosure to ensure relevance, accuracy, and stakeholders' trust in the company.